Should you choose to do so...: A replication paradigm - Richard G. Anderson (Kiel Institute for the World Economy (IfW), 2017)
This note introduces the concept of the replication paradigm, a framework that can (and should) be followed in every replication attempt. The paradigm expands, in part, on Bruce McCullough's well-known paraphrase of Berkeley computer scientist Jon Claerbout's insight - "An applied economics article is only the advertising for the data and code that produced the results" - and on the view that the primary social and scientific value of replication is to measure the scientific contribution of the inferences in an empirical study. The paradigm has four steps. First, in the "candidate study," identify and state clearly the hypotheses advanced by the study's authors. Second, provide a clear statement of the authors' econometric methods. Third, discuss the data. Fourth, discuss the authors' statistical inference. The author's purpose in this ordering is to reverse the too-frequent focus in the replication literature on "data." The correct data, of course, are critical to the replication. But "replication" as a scientific endeavor will never achieve respectability unless and until it abandons a narrow focus on data and expands its focus to the underlying scientific inferences.
Keywords: B41; 330; Replication; paradigm